A Pilot Study Investigating the Use of Mobile Technology for Coordinating Educational Plans in Inclusive Settings - Siyam, Nur (2021)
Good coordination among school staff and families leads to increased learning quality and academic success for students with special education needs and disabilities (SEND). This pilot study aims to investigate the use of mobile technology for the coordination of therapy and learning for students with SEND. This study first follows a participatory design methodology to identify the key design principles required to inform the design of a coordination mobile app for special education. Then, a mobile app (IEP-Connect) is designed and implemented with the aim of facilitating information sharing between different parties involved in the intervention of students with SEND. The proposed app uses the Individualized Educational Plan (IEP) as the focal point of coordination. The evaluation of the app focused on students with autism spectrum disorder (ASD) as their learning requires sharing information from different distributed sources. Results from the usability study revealed that the app has “good” usability and that participants were satisfied with the use of the app for recording and sharing IEP information. The results of this study provide an understanding of the ways in which a coordination app for special education could be made easy and rewarding to use.